Output feedback control of networked control systems with packet dropouts in both channels - Wang, Dong (2013)
This paper is concerned with the problem of H∞ output feedback control for networked control systems with packet dropouts in both sensor-to-controller and controller-to-actuator channels. Packet dropouts in these two links are modeled as two independent Markov chains, whose transition probability matrices are sparse so that it is easy to obtain. Moreover, late arrivals are considered in the model as well. Sufficient conditions for the solvability of design problems of H∞ output feedback controllers are presented and are dependent on the upper bounds of the number of consecutive packet dropouts. The validity of the proposed approaches are illustrated by a numerical example.